Prospective associations of protein intake parameters with muscle strength and physical performance in community-dwelling older men and women from the Quebec NuAge cohort. Issue 4 (29th January 2021) - Hengeveld, Linda M; Chevalier, Stéphanie; Visser, Marjolein; Gaudreau, Pierrette; Presse, Nancy
ABSTRACT: Background: Dietary protein has been related to muscle function in aging. Beyond total intake, parameters such as protein distribution across meals might also be important. Objectives: We aimed to examine prospective associations of different protein intake parameters with muscle strength and physical performance in community-dwelling older men and women. Methods: In total, 524 men and 574 women aged 67–84 y at baseline (T1) were followed annually for 3 y (T2, T3, T4). Outcomes included handgrip strength (kPa), knee extensor strength (kg), and physical performance (Timed Up and Go, s) at T4, and their 3-y changes (T4 minus T1). Protein intake parameters were assessed using nine 24-h recalls collected over 3 y (T1, T2, T3) and included daily total intake (g/d), number of protein-providing meals and snacks, and protein distribution across meals (expressed as CV). Associations were examined by multivariable linear regression models including all protein intake parameters simultaneously. Also, the optimal protein dose (g) per meal for the maximum effect size of total daily intake was determined. Results: Higher daily protein intake was associated with better knee extensor strength and physical performance at T4 in both sexes and less physical performance decline in women. Optimal protein doses per meal were 30–35 g in men and 35–50 g in women for these outcomes. In men, more uneven protein distribution was associated with better physical performance at T4 and less handgrip strength decline. In women, a higher number of protein-providing snacks was associated with better handgrip strength and knee extensor strength at T4 and less handgrip strength decline. In neither sex was number of protein-providing meals associated with outcomes. Conclusions: Higher daily protein intake, up to 30–50 g protein/meal, may contribute to better knee extensor strength and physical performance in generally well-functioning older men and women. More aspects of protein intake may contribute to muscle strength and physical performance than solely the daily quantity, notably the protein dose per meal.